2009
DOI: 10.1111/j.1741-4520.2008.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Derangement of chick embryo retinal differentiation caused by radiofrequency electromagnetic fields

Abstract: The possible adverse effects of radiofrequency electromagnetic fields (EMF) emitted from mobile phones present a major public concern. Biological electrical activities of the human body are vulnerable to interference from oscillatory aspects of EMF, which affect fundamental cellular activities, in particular, the highly active development process of embryos. Some studies highlight the possible health hazards of EMF, while others contest the hypothesis of biological impact of EMF. The present study was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The appearance of smaller lens epithelial cells with condensed pyknotic nuclei and damaged cytoplasm was similar to the findings reported by Bormusov et al [4]. Development is a dynamic process consisting of a highly ordered sequence of cell proliferation, differentiation, migration, and programmed cell death [2]. These events are based on endogenous ionic currents and electric fields present in the cells.…”
Section: Experimental Embryo Lenssupporting
confidence: 74%
See 2 more Smart Citations
“…The appearance of smaller lens epithelial cells with condensed pyknotic nuclei and damaged cytoplasm was similar to the findings reported by Bormusov et al [4]. Development is a dynamic process consisting of a highly ordered sequence of cell proliferation, differentiation, migration, and programmed cell death [2]. These events are based on endogenous ionic currents and electric fields present in the cells.…”
Section: Experimental Embryo Lenssupporting
confidence: 74%
“…These events are based on endogenous ionic currents and electric fields present in the cells. These fields get disrupted due to RF radiations from the cell phone that in turn affect these processes [2]. In the present study, the formation of multilayered epithelium on the anterior surface of the experiment lens and aberrantly formed posterior epithelium was probably due to the increased cell proliferation of lens epithelial cells due to 2G cell phone radiation exposure.…”
Section: Experimental Embryo Lensmentioning
confidence: 65%
See 1 more Smart Citation
“…A square piece with nerve in the centre was taken for processing for paraffinembedded preparations, and a 2-mm square portion was further taken from the right lateral margin of the above section for araldite-embedded preparations. The area of retina selected for study was chosen after our previous study (Zareen et al 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Vignal et al (2009) concluded that the studies could not show any significant effect on human eyes when exposed to long-term and low-dose radiation. Zareen et al(2009) concluded that EMF emitted by a mobile phone caused derangement of chicken embryo retinal differentiation. Demirel et al(2012) suggested that under a short period of exposure, 3G mobile phone radiation does not lead to harmful effects on eye tissue and blood in rats.…”
Section: Introductionmentioning
confidence: 99%